Atrial fibrillation is associated with anterior predominant white matter lesions in patients presenting with embolic stroke. Issue 1 (27th May 2017) - Mayasi, Yunis; Helenius, Johanna; McManus, David D; Goddeau, Richard P; Jun-O'Connell, Adalia H; Moonis, Majaz; Henninger, Nils
Abstract : Objective: High white matter hyperintensity (WMH) burden is commonly found on brain MRI among patients with atrial fibrillation (AF). However, whether the link between AF and WMH extends beyond a common vascular risk factor profile is uncertain. We sought to determine whether AF relates to a distinct WMH lesion pattern which may suggest specific underlying pathophysiological relationships. Methods: We retrospectively analysed a cohort of consecutive patients presenting with embolic stroke at an academic hospital and tertiary referral centre between March 2010 and March 2014. In total, 234 patients (53% female, 74% anterior circulation infarction) fulfilled the inclusion criteria and were included in the analyses. WMH lesion distribution was classified according to previously defined categories. Multivariable logistic regression analysis was performed to determine variables associated with AF within 90 days of index hospital discharge. Results: Among included patients, 114 had AF (49%). After adjustment for the CHA2 DS2 -VASc score (congestive heart failure, hypertension, age ≥75 years (doubled), diabetes mellitus, prior stroke/TIA (doubled), vascular disease, age 65–74 years, sex category (female)) score, WMH lesion burden as assessed on the Fazekas scale, embolic stroke pattern, infarct distribution and pertinent interaction terms, AF was significantly associated with presence of anterior subcortical WMH patches (OR 3.647, 95% CI 1.681 to 7.911, p=0.001). Conclusions: AF is associated with specific WMH lesion pattern among patients with embolic stroke aetiology. This suggests that the link between AF and brain injury extends beyond thromboembolic complications to include a cardiovasculopathy that affects the brain and can be detected and characterised by WMH.